(untitled) (Journal of the College of Basic Education, 2022)
This research is based on knowing the most important components or factors of strength that the United States of America possesses. As well as the impact of this force on the world in general and on Iraq in particular. It became the dominant country in the world. And the most important of these components and factors that made it the first country in the world in various aspects is what it possesses of natural ingredients, the most important of which is its geographical location and climate. They are the basic elements that make up the geopolitics of any country. It is characterized by its diverse geographical environment due to its wide geographical area. It is the third largest country in terms of area among North American countries. It also possesses many human components, the most important of which is the religious factor, which had a prominent role in its foreign policy. This is evident in the impact of the ideological and ideological pattern of the American decision-maker on foreign decisions and foreign policy orientations. Most of the foreign policy projects were clearly linked to prophecies The end of history is mainly inspired by the Christian Bible. The other factor is the economic factor, as the United States is the strongest economy in the world. And this is evident in the currency. The US dollar is the most traded currency in the world. It also ranked first in petroleum recycling and copper manufacturing. Militarily, it has the largest military power in the world. Thanks to what it possesses of war equipment, including aircraft and weapons, which were manufactured entirely inside the country. And this enormous power makes it intervene in all the conflicts that take place in the world. Its intervention is mandatory, and no state can prevent it. Its military bases are located in many countries of the world. This explains to us how powerful it is. And the US military power appears in the naval fleets it owns, which is the most powerful in the world. It also owns the largest and most powerful technology line in the world. And the most important thing that distinguishes it is the space field. She has the idea of ​​access to space. As well as owning many advanced companies in the computer, laptop and mobile phone industries. And many websites such as Google International, Amazon, Microsoft and Facebook. It is also one of the most powerful countries to protect against electronic bank theft. As for the political factor, it is characterized by stability in most of its orientations. The Ministry of Foreign Affairs, by virtue of its role, is a specialist and has a rich history, knowledge and deeper experience in dealing with other countries, and the employees of the US State Department are professionals and technocrats in foreign affairs.